The power of poems writing activities that teach and inspire - Ruurs, Margriet (Gainesville, FL Maupin House Pub, 2011)
With dozens of engaging and practical writing activities for students in grades 3-8, The Power of Poems makes it easy and fun to integrate poetry into your curriculum and teach to the standards, too. Margriet Ruurs guides you and your students through the writing process, from cultivating an inspiring learning environment and generating poem ideas to publishing poetry on paper and digitally. Hundreds of age appropriate poem recommendations, student examples, and writing tips make this a resource you ll return to again and again. Jump-start your students passion for reading and writing poetry and realize the power of poetry in your classroom today!
Rhymes and songs
1 2 13 15
Keywords: Poetry -- Authorship -- Study and teaching (Elementary) -- Activity programs; Poetry -- Study and teaching (Elementary)